Desarrollo de un sistema Web de control y administración para Academia Karla Guizado - Toro Bolaños, Fabian Eduardo (2023)
This project is developing at the Karla Guizado Academy in Guayaquil, which is oriented to registration of internal information. The system was developed using PHP, JS, JQuery, HTML and CSS, and MySQL.